The Effectiveness of Suggestopedia Method with Wordwall Picture in Increasing Vocabulary Mastery with Learning Disabilities - Merlin D Merlin D; siti Hajar Larekeng (Universitas Sulawesi Barat, 2018)
This study investigates the effects of Suggestopedia method with wordwall picture in increase the vocabulary mastery students of SMPLB Negeri Parepare in academic year 2016/ 2017. This method engages the students’ attentions and various fun learning activities which decreased the students’ boredom during their learning. Wordwall picture provides the students’ illustrations and ideas in their minds. It applied mixed methods research design quantitative and qualitative approaches with single group interrupted time-series design. The population are who students with learning disabilities of SMPLB Parepare in academic year 2016/2017 which consist of 11 students and the sample constitútes consist of 5 students. This research used sampling as a technique of sampling. Based on the quantitative analysis, the result showed that 1) student test were significant accorbing to the questionnaire, the result show thet the students motivation incresed. It means that suggestopedia method with wordwall picture affected the students vocebulary mastery in learning. The result also proved that students interest in learning english has a significant relationship or influence with students vocebulary score. 2) The qualitative data from questionnaire showed that students’ motivation increased. It means that Suggestopedia method with wordwall picture affected the students vocabulary, mastery in learning, it proved that Suggestopedia Method with Wordwall Picture able to increase the interest in learning English of the students with disabilities learning of SMPLB Parepare;